1998
DOI: 10.1038/sj.ejcn.1600563
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status, thyroid function and pregnancy: study of Swedish and Sudanese women

Abstract: Objective: To examine and compare the effects of pregnancy on the thyroid hormone homeostasis in two different populations with variable iodine supply. Design: A longitudinal prospective cohort study throughout pregnancy involving Swedish and Sudanese pregnant women. Setting: The subjects were enrolled consecutively during their antenatal follow-up at health centres at Nyby in Uppsala, Sweden and Omdurman in Sudan. Subjects: Fifty-one apparently healthy women from Uppsala, Sweden and twenty-eight pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 18 publications
2
33
2
Order By: Relevance
“…The current study is complementary to the comprehensive studies on iodine nutrition among pregnant women that we have conducted previously in Sudan and Sweden (Elnagar et al, 1998;Eltom et al, 1999a,b). In these studies we looked at the changes in the thyroid function associated with pregnancy in populations residing in areas with variable amounts of iodine intake as represented by these two countries.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The current study is complementary to the comprehensive studies on iodine nutrition among pregnant women that we have conducted previously in Sudan and Sweden (Elnagar et al, 1998;Eltom et al, 1999a,b). In these studies we looked at the changes in the thyroid function associated with pregnancy in populations residing in areas with variable amounts of iodine intake as represented by these two countries.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous investigation of Swedish and Sudanese pregnant women, we found that the Swedish women showed a decline in FT4 and a rise in TSH with the progression of pregnancy, while the Sudanese women with (Eltom 1999a,b) and without (Elnagar et al, 1998) goitre displayed a reduction both in FT4 and in the urinary iodine concentration (UIC), but a stable TSH within the reference range. Our interpretation of those ®ndings, as in similar other studies, was that both of these groups of pregnant women, although exhibiting different behaviour in their iodine metabolism in response to pregnancy, were likely to be in need of additional iodine intake during gestation.…”
Section: Introductionmentioning
confidence: 87%
“…Within each season, differences in UI between pregnant and lactating women were significant by median two-sample test, Po0.005. (Pedersen et al, 1993;Glinoer et al, 1995;Caron et al, 1997;Elnager et al, 1998) and Sudan (Elnager et al, 1998;Eltom et al, 2000). However, compared to European women, women in this region of Nepal are subject to additional environmental and nutritional stresses (West et al, 1999;Dreyfuss et al, 2000) that may compound the health consequences of mild-to-moderate iodine deficiency for themselves and their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…All the women were on normal diets and did not suffer from severe hyperemesis nor any known thyroid disease. Sweden is an iodine-sufficient country, and although urinary iodine (UI) concentrations were not specifically measured in the women participating in our study, in another study conducted in Sweden in 1998 [19], mean values (95% confidence interval) for 24-h urine during gestation week (GW) 11-13 were 1.40 (1.19-1.61) μmol/day, GW 24 UI 1.33 (1.14-1.51) μmol/day, GW 32, UI 1.45 (1.06-1.84) μmol/day and GW 38 UI 1.14 (0.88-1.39) μmol/day. Serum samples were stored frozen at −70 °C and thawed at room temperature, and all samples were analyzed at the same time.…”
Section: Sample Preparationmentioning
confidence: 99%